Liberating masculinities - Ratele, Kopano; National Institute for the Humanities and Social Sciences (South Afr ica) (Cape Town : HSRC Press, 2016)
"Covering a range of topics, from clothes and violent death, through a better sexual life and tradition, to race and feminism, Liberating M asculinities presents ways to understand the contestations around mascu linity and gender relations. Kopano Ratele offers both theoretically ri ch and psychologically insightful analyses to liberate men, as well as those who are involved in the making of men, from oppressive and injuri ous models of masculinity."--Back cover.
Men no longer rule over their families -- Ayashisa amateki -- At ris k of violent death -- A better (sexual) life for all -- Liberating masc ulinities -- Masculinities without tradition -- We black men -- What va lue is feminism to men?
"National Institute for the Humanities and Social Sciences"--Title p age.
Includes bibliographical references (pages 152-164) and index.
Keywords: Masculinity -- South Africa; Men -- South Africa -- Psychology; Men -- South Africa -- Social life and customs; Sex role -- South Africa